How kinship systems change : on the dialectics of practice and classification - Parkin, Robert, 1950- (Berghahn Books, 2021)
"Using some of his landmark publications on kinship, along with a new introduction, chapter and conclusion, Robert Parkin discusses here the changes in kinship terminologies and marriage practices, as well as the dialectics between them. The chapters also focus on a suggested trajectory, linking South Asia and Europe and the specific question of the status of Crow-Omaha systems. The collection culminates in the argument that, whereas marriage systems and practices seem infinitely varied when examined from a very close perspective, the terminologies that accompany them are much more restricted"-- Provided by publisher.
Keywords: Kinship.; Marriage -- Social aspects.; Cross-cousin marriage.; Kinship -- India.; Crow Indians -- Kinship.; Omaha Indians -- Kinship.; Parenté.; Mariage -- Aspect social.; Mariage des cousins croisés.; Parenté -- Inde.; Crow -- Parenté.; Omaha -- Parenté.; kinship.; SOCIAL SCIENCE / Anthropology / Cultural; Cross-cousin marriage; Kinship; Marriage -- Social aspects; India